The multidisciplinary approach to eosinophilia - Thomsen, Gunhild Nynke; Christoffersen, Mette Niemann; Lindegaard, Hanne Merete; Davidsen, Jesper Rømhild; Hartmeyer, Gitte Nyvang; Assing, Kristian; Mortz, Charlotte G.; Martin-Iguacel, Raquel; Møller, Michael Boe; Kjeldsen, Anette Drøhse; Havelund, Troels; El Fassi, Daniel; et al. (Frontiers in Oncology, 2023)
Eosinophilic granulocytes are normally present in low numbers in the bloodstream. Patients with an increased number of eosinophilic granulocytes in the differential count (eosinophilia) are common and can pose a clinical challenge because conditions with eosinophilia occur in all medical specialties. The diagnostic approach must be guided by a thorough medical history, supported by specific tests to guide individualized treatment. Neoplastic (primary) eosinophilia is identified by one of several unique acquired genetic causes. In contrast, reactive (secondary) eosinophilia is associated with a cytokine stimulus in a specific disease, while idiopathic eosinophilia is a diagnosis by exclusion. Rational treatment is disease-directed in secondary cases and has paved the way for targeted treatment against the driver in primary eosinophilia, whereas idiopathic cases are treated as needed by principles in eosinophilia originating from clonal drivers. The vast majority of patients are diagnosed with secondary eosinophilia and are managed by the relevant specialty—e.g., rheumatology, allergy, dermatology, gastroenterology, pulmonary medicine, hematology, or infectious disease. The overlap in symptoms and the risk of irreversible organ involvement in eosinophilia, irrespective of the cause, warrants that patients without a diagnostic clarification or who do not respond to adequate treatment should be referred to a multidisciplinary function anchored in a hematology department for evaluation. This review presents the pathophysiology, manifestations, differential diagnosis, diagnostic workup, and management of (adult) patients with eosinophilia. The purpose is to place eosinophilia in a clinical context, and therefore justify and inspire the establishment of a multidisciplinary team of experts from diagnostic and clinical specialties at the regional level to support the second opinion. The target patient population requires highly specialized laboratory analysis and therapy and occasionally has severe eosinophil-induced organ dysfunction. An added value of a centralized, clinical function is to serve as a platform for education and research to further improve the management of patients with eosinophilia. Primary and idiopathic eosinophilia are key topics in the review, which also address current research and discusses outstanding issues in the field.